Cross-species amplification of cassava (Manihot esculenta) (Euphorbiaceae) microsatellites: Allelic polymorphism and degree of relationship - Roa, A.C.; Chavarriaga Aguirre, Paul; Duque E., Myriam Cristina; Maya, M.M.; Bonierbale, Merideth W.; Iglesias, C.A.; Tohme, Joseph M. (2000)
Microsatellite amplification was performed on cassava (Manihot esculenta) and six other different species (all wild) of the Manihot genus. We used ten pairs of microsatellite primers previously developed from cassava, detecting 124 alleles in a sample of 121 accessions of the seven species. The number of alleles per locus ranged from four to 21 alleles, and allelic diversity was greater in the wild species than in cassava. Seventy-nine alleles, including unique ones, were detected in the wild species but were not found in the crop. The lower level of heterozygosity in some wild species probably resulted from a combination of fine-scale differentiation within the species and the presence of null alleles. Overall, microsatellite primers worked across the genus, but, with increasing genetic distance, success in amplifying loci tended to decrease. No accession of M. aesculifolia, M. carthaginensis, and M. brachyloba presented a banding pattern at locus Ga-140; neither did one appear for M. aesculifolia at locus Ga-13. Previous work with amplified fragment length polymorphism (AFLP) markers and this microsatellite analysis show that these three wild taxa are the most distant relatives of the crop, whereas the wild forms M. esculenta subsp. flabellifolia and M. esculenta subsp. peruviana appear to be the closest.